Feasibility study for platform migration from AS400 and eBO to SAP ERP - case study for Johnson & Johnson Vision Care (JJVC) / Shariza Abdul Razak - Abdul Razak, Shariza (2014)
Feasibility study for platform migration will help Johnson & Johnson Vision Care (Malaysia) to decide go/not go decision for the new project based on the feasibility study result. Objectives of this study are to identify the requirement and determine the impact for platform migration. This study used observation, document review and risk assessment method to address the migration plan. Study consists of technical, operational, and cost-benefit analysis based on specific area need to cater. Technical feasibility helps to identify the requirement for hardware and software aspect for the new platform. Cost-benefit feasibility cater for tangible and intangible benefit when change the platform. Operational feasibility determines the impact for business operational process in order to identify is there any changes to current business process. These feasibility study result will help organization to use it as a benchmark before they decide to change or upgrade their current platform.